The dual burden of obesity: decoding metabolism and female reproductive endocrinology - Chen, Yan; Wang, Rongyu; Zhang, Nannan; Xu, Liangzhi (Frontiers in Physiology, 2025)
The global prevalence of obesity continues to rise, posing a threat to health, especially among women, where obesity can lead to reproductive endocrine disorders. Adipose tissue interacts with endocrine hormones, including insulin, leptin, and sex hormones, resulting in functional abnormalities of the female hypothalamic-pituitary-ovarian axis through various central and peripheral mechanisms. At the same time, systemic inflammation, intestinal microbiota, and metabolites are also implicated in these processes, further linking metabolic imbalance to reproductive endocrine dysfunction. Therefore, targeting these co-regulatory mechanisms is expected to improve metabolic disorders and reproductive endocrine dysfunction in obese women. Strategies for treating obesity include dietary and behavioral interventions, medication, surgical treatment, and traditional and alternative medical therapies, showing benefits for improving reproductive endocrine dysfunction. This review calls on clinicians to pay attention to the impact of obesity on reproductive health in women and proposes possible intervention measures.